Filtration Algorithms of Untrustworthy Analogous Information in APCS at TPP and NPP - V. I. Nazarov; Е. V. Pronkevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers filtration algorithms of untrustworthy analogous information in APCS at TTP and NPP that make it possible to identify credibility of information transmitted through communication channels in the form of signals and which are continuously changeable in the regime of real time.